Brain control games and applications - Darmaja, Natalia (2018)
Brain-computer interface (BCI) is a study of direct communication between human brain and computer. Several types of BCI devices incorporate electroencephalography (EEG) technology. EEG-based BCI captures the pattern of electrical activity and maps them to corresponding actions. The recent commercialization of EEG-based BCI allows opportunities for brain activity research. Many companies have come up with their version of EEG-based BCI with a wide range of price and specifications. Nonetheless, despite several studies exploring the capability of EEG headset as video gaming tool, it has yet gained much recognition. This could be due to the challenging control of the headset despite rigorous training and the high price point of headsets with better accuracy. Therefore, cheaper alternative Emotiv Insight headset is used to develop a simple altered version of Tetris game called Brain Tetris. The project aimed to prove the viability of using low-end EEG headset for gaming. Problems ensued while developing and testing the game, such as training difficulty, the presence of false positive inputs, and limited commands to be used. Hence, it can be concluded that the low-end commercial EEG headsets available in the market are not yet suitable for video gaming purposes. It is not capable of replacing traditional input method due to the unstable nature of the EEG detection.